Fostering Alumni Commitment with Intercultural Competence and Social Responsibility - Rincón, Sandra S.; Rutkowski, Anne F.; Feskens, Mats (ICAReAlumni Conference Proceedings, 2023)
In contributing to advance higher education´s service mission and its internationalization´ agenda, this pilot study explores the relationship between intercultural competence (IC) and social responsibility (SR) in college graduates. It further studies whether IC and SR can positively influence alumni’s organizational commitment (OC) to the university since their commitment can support higher education as a public good and its positive impact on societies worldwide. 150 graduates of a Dutch university were surveyed. Two groups of alumni were selected: a) they either had studied in the Netherlands as international students or b) they were Dutch graduates working abroad at the time. The results show that IC has a statistically significant effect on SR, which in turn has a mediating role between IC and alumni’s commitment to the university. Given the importance of IC and SR in developing responsible global citizens, the results of this study support the benefits of teaching these competences in building common efforts to co-create solutions for the global challenges and thus, help higher education´s support for the Sustainable Development Goals.